Implementation by the Food and Drug Supervisory Agency (BPOM) of Bamboo Products in Jorong Balai Labuah Bawah, Tanah Datar - Winny Alna Marlina; Nur Ari Sufiawan; Nefy Putri Novani; Handoko Handoko (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Sumatera Volunteer Foundation was founded in 2014. The foundation is located in Jorong Balai Labuah Bawah-Lima Kaum, which is located on flat land. The main activity of the non-profit Sumatra Volunteer Foundation is a handicraft business whose main raw materials are obtained from nature Sumatra Volunteer sells goods whose raw material is bamboo, such as straws (Sumatra Straws), food made from coconut shells, gifts made from bamboo, and crafts to finance the Foundation's operational activities. In BPOM permit regulations, only straw products are permitted because they are used directly by users as drinking utensils. The sales system still uses the help of friends, family, alumni, students, and interns from the Sumatra Volunteer Foundation. The marketing activities of the Sumatra Volunteer Foundation do not yet have a BPOM permit, so consumers and potential consumers feel safer when using goods with a BPOM certificate. This activity aims to develop the craft product business at the Sumatra Volunteer Foundation by obtaining a BPOM permit. Educational activities regarding BPOM were successfully carried out with the consideration that the product could be clinically tested.